An exploratory study of listening skills of professionals across different cultures - Raina, Reeta; Roebuck, D. B.; Lee, Cheng Ean Catherine * (Zia World Press, 2014)
The significance of listening skills for the efficiency and effectiveness of individual and organizational success is starting to be recognized around the world. This study sought to explore the listening skills of working professionals from three countries – India, Malaysia and the United States of America (USA). A total of 633 completed surveys were received from working individuals within the three countries. The results show the respondents from Malaysia have lower self-perceived listening competencies compared to India and USA. The study found no significant difference on listening skill due to age differences. However, respondents within the age group of 61 to 65 years old were found to be better listeners.